Analisis Reaksi Pasar Modal Pada Peristiwa Pemilihan Gubernur Dki Jakarta Tahun 2017 - Pameswari, Ida Ayu Nirma; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 22 No 2 (2018), 2018)
Investment activity is tightly related to information contents which can affect the capital market. Through investment decision making, investors will take concerned about information from various events, including politic events. This research purpose is to explain the capital market reaction regarding the Governor election of DKI Jakarta in 2017 by observing the abnormal return and trading volume activity. This is an event study research with the sample are companies engaged in Index LQ-45 and through 11 days observation. The sampling method used purposive sampling. Data analysis technique is paired sample t-test. The result shown there is no difference of average abnormal return and trading volume activity, both before and after the election. Implications of this research theoretically give empirical evidence which strengthen the information content theory and practically could be a consideration for the investors to be thriftier in facing various events whilst making investment decision in the capital market.                                                                                                   Keywords: event study, politi  events, abnormal return, trading volume activity